'I'm unlikeable, boring, weird, foolish, inferior, inadequate': how to address the persistent negative self-evaluations that are central to social anxiety disorder with cognitive therapy. (1st December 2022) - Warnock-Parkes, Emma; Wild, Jennifer; Thew, Graham; Kerr, Alice; Grey, Nick; Clark, David M.
Abstract: Patients with social anxiety disorder (SAD) have a range of negative thoughts and beliefs about how they think they come across to others. These include specific fears about doing or saying something that will be judged negatively (e.g. 'I'll babble', 'I'll have nothing to say', 'I'll blush', 'I'll sweat', 'I'll shake', etc.) and more persistent negative self-evaluative beliefs such as 'I am unlikeable', 'I am foolish', 'I am inadequate', 'I am inferior', 'I am weird/different' and 'I am boring'. Some therapists may take the presence of such persistent negative self-evaluations as being a separate problem of 'low self-esteem', rather than seeing them as a core feature of SAD. This may lead to a delay in addressing the persistent negative self-evaluations until the last stages of treatment, as might be typically done in cognitive therapy for depression. It might also prompt therapist drift from the core interventions of NICE recommended cognitive therapy for social anxiety disorder (CT-SAD). Therapists may be tempted to devote considerable time to interventions for 'low self-esteem'. Our experience from almost 30 years of treating SAD within the framework of the Clark and Wells (1995) model is that when these digressions are at the cost of core CT-SAD techniques, they have limited value. This article clarifies the role of persistent negative self-evaluations in SAD and shows how these beliefs can be more helpfully addressed from the start, and throughout the course of CT-SAD, using a range of experiential techniques. Key learning aims: (1) To recognise persistent negative self-evaluations as a key feature of SAD. (2) To understand that persistent negative self-evaluations are central in the Clark and Wells (1995 ) cognitive model and how to formulate these as part of SAD. (3) To be able to use all the experiential interventions in cognitive therapy for SAD to address these beliefs.